2008
DOI: 10.5688/aj720241
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Mentor in Retaining Junior Pharmacy Faculty Members

Abstract: The American Association of Colleges of Pharmacy (AACP) has identified faculty retention as a top concern since 76 colleges of pharmacy reported a total of 406 vacant and/or lost positions in the 2004-2005 academic year. Since today's junior faculty members are tomorrow's leaders in pharmacy education, retention of quality faculty members is critical to our future. Mentoring is one effective method of retaining faculty members and decreasing workplace stress, especially in the area of scholarship. However, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 14 publications
(47 reference statements)
0
52
0
Order By: Relevance
“…The identified benefits were consistent with those reported in other published studies of mentoring, including increased job satisfaction, increased confidence, and successful transition to new position. 1,[3][4][5][6][7][8][9][10][11][12][13] Challenges with scheduling and documentation were identified. These challenges had been anticipated, as the Pharmacist Mentorship Program was an added responsibility of the participants, on top of their clinical work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified benefits were consistent with those reported in other published studies of mentoring, including increased job satisfaction, increased confidence, and successful transition to new position. 1,[3][4][5][6][7][8][9][10][11][12][13] Challenges with scheduling and documentation were identified. These challenges had been anticipated, as the Pharmacist Mentorship Program was an added responsibility of the participants, on top of their clinical work.…”
Section: Discussionmentioning
confidence: 99%
“…Available reports on pharmacy mentorship have focused on mentoring for pharmacy faculty members or mentorship in a research setting. [10][11][12] A recent article described a mentorship program created for pharmacists in primary care that emphasized the benefits of mentorship in helping pharmacists to integrate into a new environment. 13 St Joseph's Healthcare Hamilton is a 650-bed academic teaching hospital affiliated with McMaster University.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Fuller and colleagues suggested that in order to maintain faculty retention, developing nurturing relationships with senior faculty members to promote protégé educators is vital, demonstrating that mentoring is not only useful to pharmacy students, but also to new pharmacy faculty members, who are expected to be the future educational leaders of the profession. 84 …”
Section: Mentorship Of Pharmacy Studentsmentioning
confidence: 99%
“…Later, mentees can seek out mentors who share their vocational and psychosocial interests. 2 Formal mentoring programs and informal mentoring that occur between colleagues are not mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%
“…The role of faculty mentoring in academia is an integral component in retaining junior faculty members, reducing workload stress, and encouraging long-term growth and success. 2 Whether formal or informal, mentoring is a method of cultivating and building new leaders in an institution; it is a process that benefits mentees, mentors, and ultimately the academic institution. Mentors may become more engaged in their work and see this as a unique opportunity to impact another faculty member's career and growth.…”
Section: Introductionmentioning
confidence: 99%